Contributions of a blog to the identity, development and professionalisation of Social Education - Iñigo Rodríguez-Torre; Monike Gezuraga-Amundarain; Leire Darretxe-Urrutxi (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2024)
Social media have a special role in today's society and this is being reflected in the development of the professions. Social Education does not escape from this reality and to this we can add the lack of studies on the subject. This article presents part of the analysis carried out as part of a wider investigation into the contribution to Social Education of a blog called "Educablog", which has been running for more than 15 years. The aim is to analyse the contribution of the blog to the identity, professional development and professionalisation of Social Education, from the perspective of professional users. In this research we have opted for a qualitative methodology and we have used the lifeline where we have relied on the use of photographs to gather information. The discourse generated in the development of the dynamic shows significant contributions from "Educablog" in the professionalization, professional identity and professional development of Social Education. In the same way, it has been shown that digital media have significantly accompanied the evolution of Social Education within and outside this object of study.